1999
DOI: 10.1007/s004670050691
|View full text |Cite
|
Sign up to set email alerts
|

A limited sampling strategy for the estimation of Neoral AUCs in pediatric patients

Abstract: The improved pharmacokinetics of Neoral allows the development of an accurate estimate of the full area under the concentration time curve (AUC) from a limited sampling strategy. As no such strategy has been derived from pharmacokinetic data obtained from children on 12-hourly dosing, and as patient convenience demands shorter sampling times, we derived a limited sampling strategy from 45 AUCs obtained from 19 pediatric renal transplant patients by stepwise forward multiple regression, and prospectively tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Because measurement of the total AUC requires repeated blood sampling and is time-consuming and expensive, many surrogates have been developed for AUC determination. These include the 2 h post-dose concentration (C 2 ) monitoring [17,18,19,20] and limited sampling strategies that estimate the absorption phase or the complete AUC for CsA in adults [21,22] and children [23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Because measurement of the total AUC requires repeated blood sampling and is time-consuming and expensive, many surrogates have been developed for AUC determination. These include the 2 h post-dose concentration (C 2 ) monitoring [17,18,19,20] and limited sampling strategies that estimate the absorption phase or the complete AUC for CsA in adults [21,22] and children [23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, distribution of prediction errors or relative prediction errors did not follow either a normal or log-normal distribution; therefore, for assessment of predictive performance of different models, median prediction error and median absolute prediction error were selected as measures of bias and precision, respectively. 14 In reference to the goodness of prediction, as stated by other investigators, 11,22,33,34 prediction errors of 615% or 20% were the most common percentages that were used in clinical practice because this is the deviation from a predefined targeted value that would initiate dosage adjustment. Therefore, a deviation of 615% was used in the present study as a measure of good prediction.…”
Section: Discussionmentioning
confidence: 99%
“…These data have not been directly applied to children because there are possible theoretical differences in pharmacokinetics [15]. Retrospective studies from pediatric renal graft recipients have been performed mainly in the stable phase after transplantation and C 1 h [5], C 1.25 h [6], C 2 h [7,8], C 3 h [9], or combinations such as C 2 h and C 6 h [10] have been shown to yield the best correlation with AUC 0-4 h . Trompeter et al [11] recently reported a prospective study with CsA profiles and found a C 2 h of more than 1,500 ng/ml to be significantly superior in preventing rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed the best single time point to predict total drug exposure. Different results have been published and C 1 h [5], C 1.25 h [6], C 2 h [7,8], C 3 h [9], or combinations of single time points [10] showed the best correlation. Thirty-two children have been evaluated prospectively in the early transplant period and freedom from rejection was observed with a C 2 h of >1,500 ng/ml [11].…”
Section: Introductionmentioning
confidence: 97%